Banks and credit unions as providers of financial literacy : A complex relationship - Kalmi, Panu; Ruuskanen, Olli-Pekka (Routledge, 2022)
Banks and credit unions have become very active in the provision of financial education initiatives. There has been some skepticism regarding how genuine these initiatives are, given that financial institutions may benefit from customer misperceptions. However, financial institutions can also signal their trustworthiness with these campaigns, which may also be an important part of their social responsibility programs. Financial education also has implications for relationship banking. A bank's mission might also be a significant determinant of the type of financial education initiatives in which it engages. In this article, we review the various pros and cons of the involvement of financial institutions in financial education and try to understand why financial institutions engage in financial education. We also provide examples of financial education initiatives from Europe and the United States.
Keywords: credit unions; financial literacy; financial education; corporate social responsibility; banks (monetary institutions); fi=Taloustiede|en=Economics|